Literature and Intellectual Disability in Early Modern England - Equestri, Alice (Taylor & Francis Group, 2021)
Cover – Half Title – Series Page – Title Page – Copyright Page – Contents – List of Figures – Acknowledgements – 1 Introduction: Fools, From Popular Culture to Disability Studies – Section 1 Law – 2 The Legal Discourse of 'Idiocy' on the Stage and Page – 3 'A Fool and His Money Are Soon Parted': The Fool and Property – 4 'An You Knew My Properties Somebody Would Ha' Me': The Fool as a Ward – Section 2 Medicine and Physiognomy – 5 Nature, Wits, and Skulls: The Fool's Head – 6 Intellectual, Sensory, and Physical Disability: The Fool's Body and Face – 7 Rationalising Fools' Disability: Causes and Risk Factors – 8 Epilogue: Intellectual Disability, Embodiment, and Humour in Early Modern Literature – Bibliography – Index.
Description based on publisher supplied metadata and other sources
Keywords: Folly in literature; Fools and jesters in literature; Renaissance-England; Electronic books